Navigating the Risks of Dental Aspiration in Older Adults: A Case Study of Prompt Diagnosis and Intervention - Louise Cardoso Fava Ferreira dos Santos; Marcelo de Queiroz Pereira da Silva; Márcio Luís Duarte (Prague Medical Report, 2025)
Foreign body aspiration is a significant cause of respiratory distress in geriatric patients, often leading to severe complications if not promptly identified and treated. Dental materials account for approximately 15–20% of foreign body aspirations in adults, with symptoms that can include dyspnea, localized wheezing, and, in some cases, cyanosis and pneumonia. We report the case of a 60-year-old man who aspirated a dental crown, resulting in shortness of breath. A computed tomography scan revealed the crown lodged in the left main bronchus. The patient underwent successful bronchoscopy for foreign body removal and experienced a full recovery without complications. Neurological conditions, such as epilepsy or Parkinson’s disease, increase the risk of aspiration, particularly in elderly patients, in which symptoms may be misdiagnosed due to their nonspecific presentation. While the right bronchus is more commonly affected due to anatomical structure, foreign body aspiration in the left bronchus also warrants attention. This case underscores the importance of rapid imaging and bronchoscopy to reduce the risk of morbidity and mortality from aspiration events. Increased awareness and timely intervention are essential for improving patient outcomes in cases of dental and other foreign body aspirations in older populations.